Information assurance in biomedical informatics systems. - Schou, C.D.
The DHS recognizes that the progression from data to information to knowledge and subsequently to wisdom is a key to robust, reliable, and resilient biomedical informatics systems. The systems that enable this progression are increasingly complex. Frequently these systems are so complex that no one, including their designers, understands all their interactions and the implications of changes. This complexity combined with closely coupled systems operations creates critical systems that are both fragile and brittle. In the systems, failure of a single component may adversely affect the integrity, confidentiality, and availability of many critical systems. National security efforts cannot afford to place the security of the homeland on the backs of brittle systems.
Keywords: Biomedical informatics systems; Closely coupled systems; Confidentiality; Defense-in-depth program; Homeland security; Information assurance; Information systems; Integrity; National security; Security countermeasures